Feeding Of Calcium and Protein Macroparticle Or Microparticle With Bitter Mustard Root On Intestinal Bacteria Population And Nutrient Intake In Quail - Lilik Krismiyanto; Nyoman Sutama; Vitus Dwi Yunianto; Fajar Wahyono; Citra Ardelia; Ryan Zafi Fawwaz (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
This study aims to feeding of protein source feed ingredients in macroparticle or microparticles with the addition of bitter mustard root to the small intestinal bacteria population and nutrient intake in quails. The experimental livestock used by the layer phase quail were 200 birds with an average weight of 149 ± 10.88 g, protein feed ingredients in the form of soybean meal and fish meal, calcium comes from eggshells and mustard root powder as a prebiotic. The research design was a completely randomized design with 4 treatment and 5 replaice (each 10 bird). The treatment were P1= Feed with protein and calcium macroparticles; P2= Feed with protein and calcium microparticles; P3= Feed with protein and calcium macroparticles + bitter mustard root powder 1,2% dan P4= Feed with protein and calcium microparticles + bitter mustard root powder 1,2%. The parameters measured were population of lactic acid bacteria, coliform, pH, protein and calcium intake. Data were analyzed using analysis of variance (Anova) and different test (Duncan) on 5% level. The results showed that the use of rations with protein and calcium feed ingredients in macroparticles or microparticles with the addition of bitter mustard root powder had a significant effect (p<0,05) on population of small intestine bacteria and nutrient intake. The use of protein and calcium microparticles with the addition of 1.2% bitter mustard root powder (P4) was able to increase the population of lactic acid bacteria and nutrient intake (protein and calcium) and decreased coliform population and small intestine pH compared to other treatments (P1-P3). The conclusion is feeding of protein and calcium microparticles and addition of 1.2% bitter mustard root powder could increase the population of lactic acid bacteria, protein and calcium intake and reduce the coliform population and the pH of the small intestine.